2006
DOI: 10.1161/circulationaha.105.000828
|View full text |Cite
|
Sign up to set email alerts
|

Indices of Apoptosis Activation After Blood Cardioplegia and Cardiopulmonary Bypass

Abstract: Background— Cardioplegic arrest (CA) using cold blood cardioplegia (CBC) has been reported to reduce ischemia-reperfusion (IR)-induced myocardial injury via apoptosis. We studied key apoptotic mediators via the caspase-dependent and intrinsic pathways as well as poly(ADP)-ribosylating protein (PARP) activity in myocardial and peripheral tissues after CA and cardiopulmonary bypass (CBP). Methods and Results— Right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
4
36
2
Order By: Relevance
“…The main finding of the study is that off-pump surgery is associated with fewer alterations in gene expression linked to inflammation and apoptosis. This work completes earlier studies (3,10,11,13,14,16,23) that have focused on on-pump surgery with CPB and ischemia-CA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The main finding of the study is that off-pump surgery is associated with fewer alterations in gene expression linked to inflammation and apoptosis. This work completes earlier studies (3,10,11,13,14,16,23) that have focused on on-pump surgery with CPB and ischemia-CA.…”
Section: Discussionsupporting
confidence: 81%
“…Recent studies have used microarray technology to examine the human myocardial stress response during cardiac surgery (3,10,11,14,16,23). Ruel et al (16) used a 12,625 gene array to examine the cardiac and peripheral gene expression responses to CPB and CA in human atrial myocardium and skeletal muscle.…”
mentioning
confidence: 99%
“…Myocardial IR injury leads to oxygen-derived free radical production, membrane lipid peroxidation, and impaired postbypass contractility (20,21). Elevated oxygen-derived free radical production initiates and/or promotes apoptotic cascades leading to cell death and tissue damage (22). In this study, we showed that NAC, a potent antioxidant, attenuates NADPH oxidase-mediated ROS production and caspase-3 expression, decreases the percentage of phox and caspase-3 in neonatal rabbit hearts.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, several studies provided the evidence that the myocardial apoptosis is involved in the pathogenesis of persistent myocardial dysfunction after cardiac surgery 1 . Several mediators of apoptosis, including apoptosis-inducing factor (AIF) and cytochrome c, were activated after 10 to 20 min of cardiopulmonary bypass 17 . It had been proposed that PARP is implicated in various types of cell death by following mechanisms: (a) PARP could deplete NAD + and ATP of cells, resulting in an energy crisis; (b) PARP serves as a main substrates for caspases; and (c) PARP activation signals AIF release from mitochondria, resulting in a caspase-independent pathway of programmed cell death 6,18 .…”
Section: Discussionmentioning
confidence: 99%